Caries Risk Assessment in Children Aged 6-12 years based on Parental Knowledge and Its Relationship with BMI and DMFT in Ahvaz (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The prevalence of dental caries in childhood is one of the problems related to children’s oralhealth. The aim of this study was to determine the risk of caries in children aged 6-12 years based on parentalinformation and its relationship with BMI and DMFT in Ahvaz.Methods and materials: The necessary permits were obtained from the Ahvaz Education Department, andthen 300 samples of the city’s primary schools were selected. Students were examined with a disposabledental mirror and the number of decayed, missed, and restored permanent and deciduous teeth was recordedin the DMFT table. After that, the questionnaire was completed with the help of parents. The validity of thisquestionnaire was confirmed by 5 pediatric dentists and the reliability of this questionnaire was confirmedby conducting a pilot study on 10 children based on Cornbach coefficient of 0.85.Results: Maternal occupation was associated with moderate caries risk (p = 0.007). Economic situation wasassociated with low risk (p = 0.0001). The mean weight of the child in the high risk group was significantlyhigher than the low risk groups (p
Keywords: Caries risk assessment (CRA), DMFT, BMI